The Reference Diet Deprivation (ReDD) index: A new diet quality measure for more effective nutrition-sensitive policies - Pauw, Karl; Ecker, Olivier; Thurlow, James; Comstock, Andrew R. (World Bank, 2023)
Poor diet quality is a major cause of various forms of malnutrition and noncommunicable diseases. Tackling this public health problem is an important development policy priority; and doing so successfully requires access to reliable measures of diet quality that can be used for policy planning and evaluation purposes. Recent methodological developments have mostly focused on the costs and affordability of healthy diets. While diet costing methods are useful for assessing whether nutritionally desirable diets are achievable, they provide little information on how far consumers are from that diet, what dietary shifts are required to get closer to the diet, and how food or related policies might encourage such behavioral change.